The Influence of Financial Ratios on The Return on Assets in Multinational Companies - Rizkyanti, Mira; Herlinawati, Erna; Suryaningprang, Andre (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
PT Malindo Feedmill Tbk is hampered by a decline in profit in 2022 of 56.54% which has an impact on the return on assets (ROA) of only 0.6%. The aim of this research is to find out whether the decline in Return On Assets is affected by Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Net Profit Margin (NPM). This research uses quantitative methods and secondary data as well as purposive sampling. On the data obtained, classical assumption tests, multiple linear regression tests and partial and simultaneous hypothesis testing were carried out. The test results show that CR has no significant effect on ROA with tcount 0.709 < ttable 2.776 and sig. 0.510 > 0.05; DER has no significant effect on ROA with tcount 1.492 < ttable 2.776 and sig. 0.196 > 0.05; TATO has a significant effect on ROA with tcount 4,028 > ttable 2,776 and sig 0.010 < 0.05; NPM has a significant effect on ROA with tcount 5.079 > ttable 2.776 and sig 0.004 Ftable 5.19, and sig. 0.013 < 0.05 and contributes to ROA of 89%, the remaining 11% is influenced by other factors outside the research model.